Semantic Information on Electronic Medical Records (EMRs) through Ontologies - Suarez Barón, Marcos Javier (2013)
This work shows the development of ontology in the domain of Electronic Medical Records (EMRs). The ontology supports vocabulary and semantic information to patients. The ontology implemented begins with the, the exploration of semantic web applications, ontology design ,analysis and the use of ontological engineering in order information indexing and retrieval from and to electronic medical records. This ontology is one of other services to incorporate on current telemedicine systems.